"Locking the Door Before We Got the Keys": Racial Realities of the Charter School Authorization Process in Post-Katrina New Orleans. (January 2016) - Henry, Kevin Lawrence; Dixson, Adrienne D.
Charter schools have become the hegemonic "solution" for urban educational reform initiatives aimed at curtailing longstanding race-based educational inequities. The "common sense" of neoliberal charter schools as the cure to persistent inequality is best illustrated in the post-Katrina New Orleans educational reforms. This article will focus on a lesser explored aspect of charter schools: the charter school authorization and application process in post-Katrina New Orleans. We center on the perspectives of African American educational actors. Using data from separate but complementary studies, we argue the charter authorization and application process is a racialized site that reproduces White dominance.